Análise da função muscular e dissipação de energia em corredoras com e sem incontinência urinária de esforço: um estudo transversal - Natália Cardoso Campos (2024)
Introduction: Repetitive impact during running may be related to stress urinary incontinence (SUI) in female runners, with a prevalence ranging from 47% to 62% in this group. During the stance phase of running, the ground reaction force (GRF) increases to 3 to 4 times the body weight, causing an impact that must be absorbed and dissipated by the lower limb joints to reduce the load transmitted to the pelvis and lower lumbar spine. The repetitive transmission of impact to the pelvic region, combined with the inability of female runners to manage these demands, can compromise urinary continence mechanisms, leading to SUI symptoms. Therefore, this study investigated how female runners dissipate energy through the kinetic chain if there are differences in the musculoskeletal capacities (e.g., muscle functions) to handle the demands of running (e.g., stresses generated by impact) Methods: This study included women aged 18 to 45 years, with at least six months of running experience and a minimum of 20 km of training per week, who had no history of surgery or injury to the lower limbs and pelvis, were not pregnant, and had not undergone and were not undergoing treatment for SUI. Participants agreed to gynecological evaluation. The group of incontinent runners (GIR) included those who reported SUI symptoms during running and in the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF), with mandatory SUI symptoms during physical activities. The group of continent runners (GCR) included those without SUI symptoms and with a score of zero on the ICIQ-SF. Pelvic floor muscle function (vaginal squeeze pressure in cmH2O and endurance in seconds) was assessed using the Peritron, and maximal isometric strength of the hip external and internal rotators, trunk flexors, plantar flexors, and quadriceps (Newtons) was measured using a portable handheld dynamometer. Kinetic data, including impact absorption at the ankle, knee, and hip in the sagittal plane and shock attenuation between the tibia and femur, were analyzed during treadmill running using a 3D motion analysis system. Data with a normal distribution were analyzed using the t-test, while data with a non-normal distribution were analyzed using the Mann-Whitney test. A significance level of 0.05 was set for this study. Results: Thirty-two female runners participated in the study, with sixteen in the GIR and sixteen in the GCR. Groups were homogeneous in all sociodemographic variables. Vaginal squeeze pressure and endurance of the pelvic floor muscles, as well as maximum isometric strength tests of the hip external and internal rotators, trunk flexors, ankle plantar flexors, and quadriceps, showed no statistical differences between groups. Despite no differences in the vertical magnitude of the ground reaction force reaching the kinetic chain, the GIR exhibited lower energy absorption at the ankle, lower impact attenuation between the tibia and femur, and higher energy absorption at the hip during the stance phase of running compared to the GCR. Conclusion: No differences were observed in vaginal squeeze pressure, pelvic floor muscle endurance, or isometric maximal strength between runners with and without SUI. Runners with SUI exhibited lower joint energy absorption at the ankle and reduced shock attenuation between the tibia and femur, associated with higher energy absorption at the hip during the stance phase of running compared to the group without SUI. These findings suggest that the demands placed on the pelvic structures in female runners with SUI are greater than in continent runners, possibly resulting in tissue overload and contributing to SUI symptoms. SUI is a multifactorial condition, and a more comprehensive evaluation, taking into consideration the capacities to absorb and attenuate impact, is necessary to better understand the complex and non-linear relationships between individual capabilities, running demands, and SUI in female runners.